UPAYA MENINGKATAN HASIL BELAJAR DAN DISIPLIN DIRI SISWA DENGAN MODEL PROJECT BASED LEARNING MATA PELAJARAN FISIKA POKOK BAHASAN INDUKSI ELEKTROMAGNETIK SISWA KELAS XII IPA 4 MAN 1 KOTA CILEGON - AMIR FATAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The purpose of this research is to improve students' self-discipline on the subject of electromagnetic induction in Physics class XII IPA. 4 MAN 1 Cilegon City for the 2019/2020 school year by implementing a project based learning model, improving student learning outcomes on the subject of electromagnetic induction in Physics class XII science. 4 MAN 1 Cilegon City for the 2019/2020 academic year by applying the project based learning model. The results of the research show that the application of the project-based learning model can improve students' self-discipline in the teaching and learning process. This can be seen from the increase in student self-discipline in each cycle. In the first cycle, students' self-discipline reached 72% and became 79% in the second cycle and 84% in the third cycle. Implementation of project-based learning models can improve student learning outcomes. This can be seen from the results of the evaluation of the students' ability to master the learning material, the average value of which was 63.27 in the first cycle to 66.06 in the second cycle and 80.22 in the third cycle. ABSTRAKTujuan penelitian ini untuk meningkatkan disiplin diri siswa pokok bahasan induksi elektromagnetik pada mata pelajaran Fisika kelas XII IPA. 4 MAN 1 Kota Cilegon tahun pelajaran 2019/2020 dengan menerapkan model pembelajaran project based learning, meningkatkan hasil belajar siswa pokok bahasan induksi elektromagnetik pada mata pelajaran Fisika kelas XII IPA. 4 MAN 1 Kota Cilegon tahun pelajaran 2019/2020 dengan menerapkan model pembelajaran project based learning.Hasil penelitian diketahui bahwa penerapan model pembelajaran berbasis proyek dapat meningkatkan disiplin diri siswa dalam proses belajar mengajar. Hal ini dapat dilihat dari peningkatan disiplin diri siswa tiap siklusnya. Pada siklus I disiplin diri siswa mencapai 72 % dan menjadi 79% pada siklus II dan 84% pada siklus III. Implementasi model pembelajaran berbasis proyek dapat meningkatkan hasil belajar siswa. Hal ini dapat dilihat dari hasil evaluasi terhadap kemampuan siswa menguasai materi pembelajaran yang nilai rata-ratanya 63,27 pada siklus I menjadi 66,06 pada siklus II dan 80,22 pada siklus III.